BACKGROUND, CONCEPT AND ARCHITECTURAL FEATURES OF NFV (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The main tasks and security opportunities of network virtualization are considered. Functions (NFV), describes the design of the NFV architecture and some of the potential security issues and challenges of NFV. In addition, existing products and solutions in the field of NFV security were analyzed. and some promising lines of research in this area.